Crystalline sorbent materials for water capture and release.
By developing a new crystal adsorbent based on Prussian Blue, the problems of high energy consumption and insufficient structural stability of existing water capture materials are solved, and efficient and low-energy water capture and release are achieved, which significantly improves the cycling performance of the material.
Patent Information
- Application Number
- JP2023563216
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-15
- Filing Date
- 2022-04-14
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2042-04-14
AI Technical Summary
The existing water capture materials consume high energy during water adsorption and release, and lack structural stability and water adsorption capacity, resulting in inefficient economical in practical applications.
Using crystal adsorbents derived from Prussian Blue, a new crystal adsorbent with high water adsorption capacity, rapid adsorption and release kinetics and low thermal requirements are developed by adjusting their chemical composition and structure.
It achieves efficient and low-energy water capture and release, maintains the structural stability of the material, and significantly improves the cyclic performance of water adsorption and release.
Smart Images

Figure 0007665786000007 
Figure 0007665786000008 
Figure 0007665786000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a crystalline sorbent material for adsorbing and desorbing water. The present invention also relates to a method for capturing water from a composition containing water or water vapor, and to the use of the crystalline sorbent material for capturing water. In particular, the present invention relates to capturing water using the above crystalline sorbent material, which has favorable water sorption isotherms and optimal kinetics and thermodynamics of water absorption and release. [Background technology]
[0002] Water is one of the Earth's most fundamental resources; plants, animals, and humans all require fresh water for survival. Water is also used in large quantities in agricultural and industrial processes. Global demand for water is projected to increase by 55% between 2000 and 2050. Much of this demand is driven by population growth in water-scarce regions.
[0003] Thus, for example, there is a continuing and growing need to provide water in purified form from gaseous and liquid sources that contain water vapor or water, respectively, and other components or impurities. The majority of water on Earth is salt water, e.g., seawater or brackish water, which is a combination of seawater and fresh water. Fresh water / pure water can be produced from seawater or, to a lesser extent, brackish water. In these processes, the concentration of dissolved salts and other contaminants is reduced to result in fresh water / purified water. However, many of these existing purification and desalination methods require significant amounts of energy.
[0004] Atmospheric water vapor is an underutilized natural water resource that has the potential to produce purified water from the air, and is potentially sustainable. In addition, humidity control in heating, ventilation, and air conditioning (HVAC) systems involves removing water from the air to create a less humid environment. Traditional HVAC systems use a significant amount of energy, and therefore even a small reduction in energy consumption can be extremely beneficial.
[0005] Research into water capture materials has focused on sorbent materials, such as zeolites and silicas, known as desiccants when used for water capture. These desiccant materials contain many binding sites for the adsorption of small molecules such as water, and are also used in related applications such as carbon dioxide capture and gas separation. However, water capture and delivery using these materials is too energy intensive to be economically viable as a desorption method for recovering water, which requires significant heating.
[0006] More recently, interest has been focused on metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). However, like zeolites and silicas, many of these materials are not commercially viable. For example, materials that often possess highly distorted and rigid three-dimensional structures may have poor recyclability, and the structures collapse when subjected to reversibility tests due to low thermal and / or hydrolytic stability. In addition, many such materials have low working capacity, which may be caused by a low density of binding sites, resulting in poor water absorption and / or unfavorable adsorption profiles. Furthermore, some of these materials have strong water binding sites, which means high energy requirements for recycling.
[0007] Therefore, there is a need for a new class of sorbent materials that can capture water vapor over a range of humidity levels and provide a low energy footprint for recycling. Summary of the Invention
[0008] Prussian blue (Fe[Fe(CN)6] 0.75Prussian blue (Pb-xH2O) is a crystalline sorbent material discovered in the 18th century that has been widely used as a pigment. The structure of Prussian blue allows for numerous substitution and interruption modifications of its chemical composition to give a class of compounds called PB analogues (PBAs). PBAs are a generally promising class of sorbents due to their high capacity for water sorption into the pore structure and excellent structural stability.
[0009] Formula (Zn[Co(CN)6] 0.667 One PBA material based on Zn and Co, with a molecular weight of 0.1-0.4H2O (referred to herein as ZnCo), was found to adsorb large amounts of water (about 32 wt%) when the material was in the cubic phase (Roque, J.; Reguera, E.; Balmaseda, J.; Rodriguez-Hernandez, J.; Reguera, L.; del Castillo, LF, Porous hexacyanocobaltates(III): Role of the metal on the framework properties. Microporous Mesoporous Mater. 2007, 103, 57-71). However, when ZnCo is subjected to moderate stress, such as heating to 60°C, it transforms into a hexagonal phase, in which it exhibits little or no water absorption. This situation is experienced by sorbent materials during typical water capture processes, particularly during the desorption step. Therefore, the previously reported ZnCo is not suitable for use as a sorbent material in water capture processes.
[0010] Formula Zn 3-a Fe aAn iron-containing analogue of ZnCo, referred to herein as FeZnCo, with [Co(CN)6]2·nH2O, where a>0.2, has also been reported (Krap, CP; Zamora, B.; Reguera, L.; Reguera, E., Stabilization of cubic and rhombohedral phases of zinc hexacyanocobaltate (III). Microporous Mesoporous Mater. 2009, 120, 414-420). The water sorption performance of this material was not reported.
[0011] One object of the present invention, inter alia, whether defined herein or elsewhere, is to provide a method of capturing water or to provide an alternative to existing crystalline sorbent materials that addresses at least one shortcoming of crystalline sorbent materials and / or the prior art. For example, one object of the present invention may be to provide a method of capturing water using a crystalline sorbent material that has high water absorption, rapid sorption and desorption kinetics, and low heat required for cycling. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 shows a comparison of the calculated PXRD pattern for ZnCo with the experimentally obtained PXRD patterns for cubic and hexagonal phases of ZnCo. [Diagram 2] FIG. 1 shows a comparison of the calculated PXRD pattern for ZnCo with the experimental PXRD patterns for Examples 1 and 9 measured at 25° C. [Diagram 3] 1 is a scanning electron microscope image of a paper composite. [Figure 4] FIG. 1 shows the VT-PXRD patterns of Example 1 at 25° C. to 240° C. [Diagram 5]FIG. 1 shows water sorption isotherms for Example 1 (ROS-038X), Example 9 (ROS-038Y), Syloid® AL-1, and Zeolite 13X measured at 27° C. [Figure 6] FIG. 1 shows water absorption in wt % versus K+ content for example materials of Examples 1-9. [Figure 7] FIG. 1 shows the water sorption performance of ZnCo materials. [Figure 8] FIG. 1 shows the water sorption performance of FeZnCo materials. [Figure 9] FIG. 1 shows the results of these water cycling tests of Example 1 (ROS-038X) for 135 cycles. [Figure 10] FIG. 13 shows similar test results for a comparative FeZnCo sorbent material. [Figure 11] FIG. 1 shows these water cycling experiments of Example 11 (ROS-038X) paper composite for 135 cycles. [Figure 12] FIG. 1 shows comparative results of a water cycling experiment of Example 1 (ROS-038X) versus Syloid® AL-1 for 17 cycles. [Figure 13] FIG. 1 shows these water cycling experiments of Example 11 (ROS-038X) paper composite for 17 cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] According to aspects of the present invention there are provided novel crystalline sorbent materials, methods and uses as set out in the accompanying claims. Other features of the invention will be apparent from the dependent claims and from the following description.
[0014] According to a first aspect of the present invention, a compound of formula: A b M'[M(CN)6] y nH2O (wherein A is a Group 1 metal; b is 0.001 to 0.3; M' is a transition metal; M is iron or cobalt; y is 0.65 to 0.80; and n is 0 to 7). A crystalline sorbent material is provided.
[0015] Suitably, the chemical composition of the crystalline sorbent material may be measured within a tolerance of 1%, for example 0.5% or 0.2%. Methods for measuring the chemical composition of crystalline sorbent materials are known to those skilled in the art and include measurement using inductively coupled plasma optical emission spectroscopy (ICP-OES), as described below.
[0016] The present invention relates to a crystalline sorbent material. Suitably, the crystalline sorbent material of this first aspect is solid at room temperature and pressure, i.e. 25° C. and 1 atm.
[0017] In the above formula, n is an integer from 0 to 7. Preferably, n is an integer from 3 to 6.
[0018] M' is a transition metal. Preferably, M' is a first row transition metal. Preferably, M' is selected from manganese, copper, iron, cobalt, zinc, chromium, vanadium, and nickel. Preferably, M' is zinc.
[0019] M is iron or cobalt. Preferably, M and M' are different. Preferably, M is cobalt.
[0020] In some embodiments, M' is zinc and M is cobalt. In such embodiments, the crystalline sorbent material is suitably represented by the formula A b Zn[Co(CN)6] y nH2O (wherein A is a Group 1 metal; b is 0.001 to 0.3; y is 0.65 to 0.80; and n is 0 to 7).
[0021] A is a Group 1 metal. Preferably, A is selected from lithium, sodium, and potassium. Preferably, A is potassium.
[0022] In some embodiments, A is potassium, M' is zinc, and M is cobalt. In such embodiments, the crystalline sorbent material is suitably represented by the formula (K b Zn[Co(CN)6] y .nH2O) (wherein b is 0.001 to 0.3, y is 0.65 to 0.80, and n is 0 to 7).
[0023] b is between 0.001 and 3. In some embodiments, b is between 0.005 and 0.12. In such embodiments, the crystalline sorbent material is suitably a crystalline sorbent material having the formula (K b Zn[Co(CN)6] y .nH2O), where b is 0.005 to 0.12, y is 0.65 to 0.80, and n is 0 to 7. Preferably, y is 0.66 to 0.71. In such embodiments, the crystalline sorbent material may be considered to have a relatively low potassium content and may be referred to as ROS-038X sorbent material.
[0024] In some embodiments, b is between 0.12 and 0.3. In such embodiments, the crystalline sorbent material is suitably a crystalline sorbent material having the formula (K b Zn[Co(CN)6] y .nH2O), where b is 0.12 to 0.3, y is 0.65 to 0.80, and n is 0 to 7. Suitably, y is 0.70 to 0.77. In such an embodiment, the crystalline sorbent material may be considered to have a relatively high potassium content and may be referred to as ROS-038Y sorbent material.
[0025] The crystalline sorbent material of this first embodiment preferably comprises a crystal lattice that extends in three dimensions. The crystalline sorbent material preferably comprises a porous structure that includes pores suitable for sorbing water upon exposure to water vapor or liquid water.
[0026] Crystalline sorbent materials are preferably formed of unit cells that repeat in three dimensions to form a three-dimensional lattice structure. As known to those skilled in the art, a unit cell is characterized by six parameters. These parameters are the three sides (a, b, and c) and the angles between them (α, β, and γ). Using these parameters, a unit cell can be defined as cubic, tetragonal, orthorhombic, monoclinic, hexagonal, rhombohedral, or triclinic.
[0027] Preferably, the crystalline sorbent material has a cubic unit cell with lattice parameters in the range 1.00 to 1.06 nm. The crystalline sorbent material may preferably be of a cubic phase with unit cell parameters a=b=c=1.02 nm and 90 degree angles.
[0028] Crystalline sorbent materials may also be defined by the space group Fm-3m, which describes the symmetry of the material.
[0029] Preferably, the crystalline sorbent material is thermally stable. By this is meant that the crystalline sorbent material does not decompose when heated at moderate temperatures. Preferably, the crystalline sorbent material is stable at temperatures above 150°C.
[0030] Preferably, the crystalline sorbent material is hydrolytically stable. By this is meant that the crystalline sorbent material does not degrade when exposed to water or water vapor. Preferably, the crystalline sorbent material is stable when exposed to 40° C. and 75% RH for 3 months.
[0031] Suitably the crystalline sorbent material does not undergo a phase transition to the hexagonal phase when heated to a temperature of at least 60°C, such as at least 80°C or at least 100°C.
[0032] Suitably the crystalline sorbent material does not undergo a phase transition to the hexagonal phase when heated in a vacuum at a temperature of at least 30°C, such as at least 40°C.
[0033] The inventors have surprisingly found that A + It has been found that the presence of cations stabilizes the cubic phase of the crystalline sorbent material, thereby overcoming the problem of phase transformation to the hexagonal phase that occurs in known PBAs, such as ZnCo.
[0034] This stable cubic phase structure preferably provides a stable porous structure that includes pores suitable for sorbing water upon exposure to water vapor or liquid water. Thus, water can preferably enter the pores of the crystalline sorbent material. The water is preferably held within the pores by intermolecular interactions. This may be thought of as a method of adsorbing water in the bulk of the crystalline sorbent material. In another sense, this may be thought of as a method of adsorbing water molecules on the surface of the crystalline sorbent material, whether on the exterior surface of the material or on the interior surfaces of pores contained within the crystal structure of the crystalline sorbent material.
[0035] With respect to the structure of Prussian blue-type compounds, these materials are known to have highly complex structures with defect sites that are not amenable to characterization using standard structural methods. The water sorption performance of the crystalline sorbent material of the present invention is believed to be almost entirely due to these defect sites, which may lack Co(CN)6 units. Without being bound by theory, it is believed that the potassium ions in the crystalline sorbent material of the present invention are located in the pores created by these defect sites, thereby improving the stability of the cubic phase material.
[0036] These crystalline sorbent materials of the first embodiment are believed to function primarily by absorbing water into pores in their crystalline structure. The terms "trapping" or "sorbing" are used herein to describe a process that can be thought of as either adsorbing or absorbing.
[0037] As used herein, the terms "adsorb," "wick," "adsorbed," "wicked up," "adsorbing," and "wicking" are used to refer to the process of the invention in which water is absorbed (i.e., captured) by the crystalline sorbent material, regardless of whether the process of the invention is considered a true "adsorbing" or "wicking" process.
[0038] The term "releasing" is used herein to refer to the desorption process.
[0039] The inventors have surprisingly found that the crystalline sorbent materials of this first embodiment can have desirable water capture properties for use in industrial water capture methods and devices. For example, the crystalline sorbent materials can have relatively high water absorption capacity and rapid kinetics of water adsorption and desorption, which are particularly advantageous in industrial water capture where water delivery over time is a key factor in the economic viability of such methods.
[0040] For example, the crystalline sorbent material suitably has a water absorption capacity of at least 15% by weight, preferably at least 20%, at least 25%, at least 30%, or at least 35% by weight.
[0041] The crystalline sorbent material has the formula (K b Zn[Co(CN)6] y In embodiments having a water absorption capacity of 0.005 to 0.12, y to 0.65 to 0.80, and n to 0, 7 (i.e., a ROS-038X sorbent material), the water absorption capacity of the crystalline sorbent material is preferably greater than 25% by weight, preferably greater than or about 30% by weight.
[0042] The crystalline sorbent material has the formula (K b Zn[Co(CN)6] yIn an embodiment having a water absorption capacity of 0.12 to 0.3, y to 0.65 to 0.80, and n to 0, (i.e., a ROS-038Y sorbent material), the water absorption capacity of the crystalline sorbent material is preferably greater than 20% by weight, preferably approximately 20 to 25% by weight.
[0043] Preferably, the crystalline sorbent material of this first embodiment has fast kinetics of adsorption. Preferably, the crystalline sorbent material reaches at least 50% full load with water within 5 minutes at ambient temperature and ambient relative humidity. Preferably, the crystalline sorbent material reaches at least 80%, such as 90% full load with water within 10 minutes at ambient temperature and ambient relative humidity. Preferably, the crystalline sorbent material can be considered to be fully loaded with water (i.e. at least 95% full load) within 10 minutes at ambient temperature and ambient relative humidity.
[0044] Preferably, crystalline sorbent materials have fast kinetics of desorption. Preferably, the adsorption and desorption steps occur at similar rates and follow similar paths in crystalline sorbent materials. The hysteresis of crystalline sorbent materials is preferably small, preferably with approximately no difference between the adsorption and desorption threshold pressures. Hence, the adsorption-desorption process is preferably reversible.
[0045] Preferably, desorption occurs at a temperature of less than 75° C. Preferably, desorption occurs at a temperature of less than 70° C., for example less than 65° C. Preferably, desorption occurs at a temperature of less than 60° C., less than 55° C., or less than 50° C. Thus, the crystalline sorbent materials of the present invention are advantageously capable of desorbing water (i.e., being regenerated in successive water sorption cycles) using a relatively low amount of thermal energy compared to known sorbent materials. This reduces the energy consumption, and therefore the environmental impact, of water capture methods using crystalline sorbent materials compared to known water capture methods.
[0046] Preferably, the crystalline sorbent material retains its high water capacity and fast kinetics of adsorption and desorption over repeated cycles of sorption and desorption during use. Preferably, the water capacity and kinetics of adsorption and desorption remain substantially unchanged over 100 cycles of sorption and desorption, preferably over 1000 cycles of sorption and desorption, preferably over 2000 cycles or over 10000 cycles of sorption and desorption.
[0047] Because of these advantages, the crystalline sorbent materials can be effectively and efficiently used in a variety of processes, such as in HVAC systems and in desalination processes. The captured water can be removed from the crystalline sorbent materials to advantageously provide a supply of purified water for the various uses described herein.
[0048] Without being bound by theory, it is believed that the crystalline sorbent materials used in the present invention preferentially capture water molecules due to the material having a pore size (effective pore size) and pore chemistry that is complementary to water and favors water adsorption. Such materials can provide superior water selectivity and capacity, as further demonstrated below.
[0049] According to a second aspect of the present invention there is provided a method for preparing a crystalline sorbent material according to the first aspect, the method comprising: (a)B c [M(CN)6] source M'X x reacting with a source; and (b) obtaining a crystalline sorbent material; Including, wherein B is H or a Group 1 metal; c is 2 to 4; M' is a transition metal; M is iron or cobalt; X is an anion; and x is 1 to 4. A method is provided.
[0050] Preferably the method is carried out in an aqueous solution, preferably in water. Hence the method of this second aspect preferably comprises: (a) Underwater B c[M(CN)6] source M'X x reacting with a source; and (b) precipitating the crystalline sorbent material from the water; Including, wherein B is H or a Group 1 metal; c is 2-4; M' is a transition metal; M is iron or cobalt; X is an anion; and x is 1-4.
[0051] Carrying out the process in water preferably provides an environmentally friendly method for preparing crystalline sorbent materials that avoids the adverse environmental impacts associated with using organic solvents. Preferably, the process produces minimal by-products and may be considered a green chemistry process. Preferably, the process is easily scalable while retaining these advantages.
[0052] Preferred features of the first aspect of the invention also apply to this second aspect.
[0053] The method of this second aspect comprises the step of: b M'[M(CN)6] y · To provide a crystalline sorbent material having nH2O.
[0054] Suitably, step (a) comprises the step of: b Preferably, A b The atom source used in step (a) is B c [M(CN)6] substance.
[0055] B used in step (a) c In the [M(CN)6] material, B is H or a Group 1 metal. In some embodiments, B is a Group 1 metal, which is equivalent to A as defined for the crystalline sorbent material of the first aspect. Thus, in such embodiments, B c is the A of crystalline sorbent material bPreferably, B is potassium. Preferably, M is cobalt. Preferably, B is potassium and M is cobalt.
[0056] c is 2 to 4. The value of c is preferably varied to obtain a neutral compound. Preferably, c is 3.
[0057] In some embodiments, B c The [M(CN)6] substance is K3[Co(CN)6].
[0058] In some embodiments, B is a hydrogen cation, such as a proton. c The [M(CN)6] source preferably contains a quantity of a Group 1 metal A to provide atom A in the crystalline sorbent material. In such an embodiment, the method preferably provides a crystalline sorbent material having a relatively small amount of such A atom. In such an embodiment, B c The [M(CN)6] source may contain trace amounts of Group 1 metal A, for example, 1 to 10 ppm A, or 2 to 6 ppm A. c The [M(CN)6] material is preferably H3[Co(CN)6] and preferably contains a trace amount of potassium, for example, 1 to 10 ppm potassium, or 2 to 6 ppm potassium, for example, approximately 4 ppm potassium. c The amount of A in the [M(CN)6] or H3[Co(CN)6] material can be determined by ICP-OES as described below.
[0059] M'X used in step (a) x wherein X is an anion. Preferably, X is selected from chloride, fluoride, bromide, nitrate, nitrite, sulfate, and phosphate. In a preferred embodiment, X is selected from nitrate and sulfate. The value of x is preferably varied to obtain a neutral compound.
[0060] M'Xx may suitably exist in a hydrated form and therefore may include additional water molecules.
[0061] Preferably, M' is Zn. Preferably, M'X x is Zn(SO4)2·7H2O, Zn(NO3)2·6H2O, or ZnCl2.
[0062] Advantageously, this second aspect comprises a compound of formula (K b Zn[Co(CN)6] y A method for preparing a crystalline sorbent material of (nH2O), comprising: (a) B3[Co(CN)6] source in water with ZnX x reacting with a source; and (b) precipitating the crystalline sorbent material from the water; Including, where B is H or K, and if B is H, step (a) comprises reacting a K source with a B3[Co(CN)6] source and ZnX x reacting with a source; In the formula, b is 0.005 to 0.12, y is 0.65 to 0.80, n is 0 to 7, X is an anion, and x is 1 to 4. A method is provided.
[0063] The crystalline sorbent materials of the present invention may be considered analogues of Prussian Blue. In the Prussian Blue structure of formula M[M'(CN)6], M and M' occupy alternating lattice vertices and are bonded to cyanide ions (CN - ) in an octahedral coordination. Charge balance is achieved by the distribution of vacancies within the unit cell. These vacancies can form a porous structure with a larger surface area.
[0064] The inventors have unexpectedly discovered that slight differences in the number of octahedral units can affect the structural vacancies present within the unit cell, resulting in crystalline sorbent materials having water sorption isotherms with highly favorable characteristics for water uptake and release.
[0065] According to a third aspect of the present invention there is provided a method for capturing water from a composition comprising water and / or water vapour, the method comprising: (i) Formula A b M'[M(CN)6] y providing a crystalline sorbent material of nH2O; and (ii) contacting the crystalline sorbent material with a composition comprising water; Including, Upon contact with a composition containing water and / or water vapor, the crystalline sorbent material sorbs water; wherein A is a Group 1 metal; b is 0.001 to 0.3; M' is a transition metal; M is iron or cobalt; y is 0.65 to 0.80; and n is 0 to 7. A method is provided.
[0066] The crystalline sorbent material used in the method of this third aspect may have any of the features and advantages described in relation to the first aspect.
[0067] Preferably, in the method of the first aspect, steps (i) and (ii) are carried out consecutively, preferably in the order of step (i) followed by step (ii).
[0068] In some embodiments, the method of this third aspect may involve the use of more than one crystalline sorbent material, in such embodiments, reference to a crystalline sorbent material includes mixtures.
[0069] In the method of this third aspect, the composition comprising water or water vapor may be any composition comprising water and / or water vapor. The composition may be a gaseous composition comprising water vapor, preferably air. The composition may be a liquid composition comprising water, preferably a complex liquid composition comprising water and one or more additional components, for example salt water, brackish water, such as sea and ocean water, or waste water.
[0070] In some embodiments, water may not be a major component of the composition, for example, present as an impurity. In such embodiments, the method of the third aspect may be used to remove water or water vapor, for example, to produce an anhydrous composition or to provide dehumidified air.
[0071] In some embodiments, water is the major component of a composition, e.g., a liquid aqueous composition that contains impurities such as dissolved salts, etc. In such embodiments, the method of this third aspect can be used to provide purified water.
[0072] In some embodiments, compositions containing water or water vapor may be treated prior to use in the present invention, hi preferred embodiments, compositions containing water or water vapor are not treated prior to use.
[0073] Step (ii) of the method of the third aspect involves contacting the crystalline sorbent material with a composition comprising water or water vapour to entrap water in the crystalline sorbent material. Suitably the crystalline sorbent material is directly contacted with the composition comprising water or water vapour.
[0074] In embodiments in which the composition is a liquid composition comprising water, the liquid composition comprising water may be any body of water. The liquid composition comprising water may be still or standing water, or it may be moving water, for example, running water.
[0075] Preferably, contact of the crystalline sorbent material with a composition comprising water or water vapor is sufficient to allow adsorption or wicking of water from the composition comprising water and / or water vapor into the pores of the crystalline sorbent material. The crystalline sorbent material is preferably provided in a form that facilitates contact with a composition comprising water or water vapor.
[0076] The crystalline sorbent material may be provided as a powder. Suitably, when contacted with a composition comprising water or water vapor, the crystalline powder may become wet. In embodiments where the composition is a liquid composition comprising water, the sorbent powder may be dispersed in the liquid composition comprising water.
[0077] The crystalline sorbent material may be provided in the form of a shaped body, such as pellets, pellets, or tablets. In embodiments where the composition comprising water is a liquid composition comprising water, such pellets, pellets, or tablets may be placed in or exposed to the liquid composition comprising water.
[0078] The crystalline sorbent material may be provided as a sheet material.
[0079] The crystalline sorbent material may be provided as part of the membrane, in such embodiments, a composition including water and / or water vapor may flow across or through the membrane.
[0080] Preferably, the crystalline sorbent material is provided in or supported on a support, suitably the support can help maintain the morphology of the crystalline sorbent material under normal conditions of use.
[0081] The crystalline sorbent material is preferably disposed on the support in a configuration to ensure maximum sorption. The crystalline sorbent material may be disposed on the surface of the support or may be incorporated within the body of the support.
[0082] The support may be selected from any suitable polymeric, plastic, metallic, resinous and / or composite material. A person skilled in the art is familiar with these types of materials and is able to select the most appropriate support for the device.
[0083] In some embodiments, the support is a polymeric material. In one embodiment, the support comprises an acrylic polymer. Suitable acrylic polymers include HYCAR® 26410, available from Lubrizol Corporation.
[0084] In one embodiment, the support comprises a cellulosic material, such as paper. The support may comprise a composite of paper and another polymer.
[0085] The crystalline sorbent material and the support may be considered to provide a sorbent composition.
[0086] The sorbent composition preferably comprises from 10 to 90% by weight of the crystalline sorbent material, preferably from 30 to 70% by weight of the crystalline sorbent material, preferably from 40 to 60% by weight of the crystalline sorbent material, preferably approximately 50% by weight of the crystalline sorbent material.
[0087] The sorbent composition preferably comprises 10-90% by weight of the crystalline sorbent material and 90-10% by weight of the support, preferably 30-70% by weight of the crystalline sorbent material and 70-30% by weight of the support, preferably 40-60% by weight of the crystalline sorbent material and 60-40% by weight of the support. Preferably the sorbent composition consists essentially of the crystalline sorbent material and the support. Preferably the sorbent composition consists of the crystalline sorbent material and the support.
[0088] In some embodiments, the crystalline sorbent material is contacted with running water or tap water. The crystalline sorbent material can be positioned such that a liquid composition comprising water falls onto the crystalline sorbent material. For example, the crystalline sorbent material can be placed under a stream of running water.
[0089] The crystalline sorbent material may be positioned such that a composition comprising water or water vapor moves through or across the crystalline sorbent material, in some embodiments, a composition comprising water and / or water vapor may flow through a channel and the crystalline sorbent material may be provided along or within the channel.
[0090] In some preferred embodiments, the crystalline sorbent material is contacted with a composition comprising water or water vapor contained within a container, which may include a means for delivering gas and / or liquid to the container.
[0091] Suitably, in step (b), the crystalline sorbent material is at least partially immersed in a composition comprising water and / or water vapour.
[0092] In some embodiments, the crystalline sorbent material can be completely immersed in a composition comprising water or water vapor.
[0093] Suitably, the crystalline sorbent material is provided in a sorbent rotor which rotates portions of the crystalline sorbent material in and out of contact with a composition comprising water or water vapor.
[0094] In some embodiments, the method of the third aspect comprises the further step (iii) of desorbing water from the crystalline sorbent material as water vapor. Suitably, step (iii) is carried out after step (ii).
[0095] Suitably, desorption occurs when the crystalline sorbent material is subjected to a stimulus, such as a change in humidity, a change in pressure, a change in temperature, or a change in two or more of pressure, temperature, and humidity, hi some embodiments, the stimulus is brought about by separating the crystalline sorbent material from a liquid composition comprising water.
[0096] Desorption can occur with the application of external energy. In some preferred embodiments, desorption occurs with a decrease in humidity and / or an increase in temperature.
[0097] Step (iii) may include contacting the crystalline sorbent material with a moist gas mixture stream, e.g., an air stream. In some preferred embodiments of step (iii), air may flow over or through the crystalline sorbent material, or a moist air stream is directed over or through the crystalline sorbent material.
[0098] In a preferred embodiment of step (iii), the crystalline sorbent material is contacted with warm air as part of a heat swing process, and / or with dry air as part of a humidity swing process, and / or is exposed to a vacuum as part of a vacuum swing process.
[0099] In some embodiments, step (iii) involves contacting the crystalline sorbent material with warm air having a temperature between 2°C and 140°C, preferably between 20°C and 100°C, such as between 25°C and 90°C, or between 30°C and 80°C.
[0100] Preferably the warm air has a temperature between 35°C and 100°C, preferably between 35°C and 75°C, for example between 40°C and 60°C.
[0101] In some embodiments of step (iii), the crystalline sorbent material is suitably contacted with dry air having a humidity of less than 50 grains, preferably less than 30 grains, and more preferably less than 20 grains. Grain units are known to those skilled in the art and are an absolute measure of how much water is present in 1 lb of air under any temperature conditions.
[0102] In some embodiments, step (iii) comprises applying a vacuum to the crystalline sorbent material to desorb water / water vapor. Preferably, a vacuum is applied at a pressure of 1 Torr or less (0.005 Torr), preferably 0.1 Torr or less (0.005 Torr). The vacuum applied to the crystalline sorbent material in step (iii) may advantageously be provided by readily available vacuum pumping equipment.
[0103] Suitably, during step (iii), the water molecules are desorbed as gaseous water molecules or water vapour.
[0104] Preferably, the crystalline sorbent material is resistant to at least 120 cm of water vapor when subjected to a stimulus, such as a change in temperature or a change in humidity. 3 / material cm 3 Preferably, the crystalline sorbent material, when stimulated, desorbs at least 130 cm of water vapour. 3 / material cm 3 , e.g., water vapor at least 140 cm 3 / material cm 3 Preferably, the crystalline sorbent material desorbs at least 150 cm of water vapour when stimulated. 3 / material cm 3 Remove and put on.
[0105] Preferably, the crystalline sorbent material desorbs at least 20% of the captured water within 5 minutes under ambient conditions of temperature and humidity (27°C, 1 atm). Preferably, the crystalline sorbent material desorbs at least 30%, such as at least 40%, of the captured water within 10 minutes under ambient conditions of temperature and humidity. Preferably, the crystalline sorbent material desorbs at least 50% of the captured water within 1 hour under ambient conditions of temperature and humidity.
[0106] Preferably, in step (ii), at least 10% by weight of water, preferably at least 15% by weight, such as at least 18% by weight, for example at least 20% by weight, or at least 25% by weight, based on the weight of the crystalline sorbent material, is captured in 10 minutes.
[0107] The inventors have discovered that the use of certain crystalline sorbent materials provides superior working capacity performance as compared to known water sorbent materials, such as Syloid® Al-1.
[0108] The inventors have discovered that the use of certain crystalline sorbent materials provides superior water absorption performance compared to known water sorbent materials, such as Syloid® Al-1.
[0109] The inventors have discovered that the use of certain crystalline sorbent materials provides superior water delivery performance compared to known water sorbent materials, such as Syloid® Al-1.
[0110] In some embodiments, the method of the third aspect comprises the further step (iv) of condensing the desorbed water vapor to provide liquid water. Suitably, step (iv) is performed after step (iii).
[0111] Water vapor can condense without an external stimulus due to the temperature and / or humidity conditions of the environment it is in. In a preferred embodiment, water vapor desorbed from the crystalline sorbent material is condensed using an external stimulus.
[0112] Methods for condensing water vapor into liquid water are known to those skilled in the art. For example, the water vapor can be cooled or pressurized. The cooling step can be active or passive.
[0113] In a preferred embodiment, the sorption and desorption of water is reversible.
[0114] In particularly preferred embodiments, sorption and desorption are reversible over multiple cycles, preferably thousands of cycles.
[0115] The water delivered from the crystalline sorbent material is preferably ultrapure water. This water vapor is preferably condensed to provide liquid ultrapure water.
[0116] Ultrapure water is meant to refer to water that is free of any contaminant species, such as organic and inorganic compounds and dissolved gases. Preferably, there will be less than 100 ppm of contaminant species, preferably less than 50 ppm, for example less than 20 ppm. In some embodiments, water containing less than 10 ppm or less than 5 ppm of contaminant species may be provided.
[0117] Therefore, in a fourth aspect, the present invention provides a method of delivering water to a locus from a composition comprising water or water vapour, the method comprising: (1) Formula A b M'[M(CN)6] y Providing a crystalline sorbent material of nH2O; (2) contacting the crystalline sorbent material with water or water vapor to entrap water in the crystalline sorbent material; (3) optionally, transporting and / or storing the crystalline sorbent material; (4) applying a stimulus to the crystalline sorbent material to effect desorption of water retained in the crystalline sorbent material; and (5) collecting the desorbed water in place; Including, wherein A is a Group 1 metal; b is 0.001-0.3; M' is a transition metal; M is iron or cobalt; y is 0.65-0.80; and n is 0-7.
[0118] Preferably, in the method of the fourth aspect, steps (1) to (5) are performed consecutively in numerical order.
[0119] Where appropriate, preferred features and advantages described in relation to the first and third aspects apply to this fourth aspect.
[0120] According to a fifth aspect of the present invention, there is provided a method for capturing water or water vapor from a composition containing water or water vapor, comprising the formula A b M'[M(CN)6] y There is provided the use of a crystalline sorbent material of the formula: nH2O, where A is a Group 1 metal; b is 0.001 to 0.3; M' is a transition metal; M is iron or cobalt; y is 0.65 to 0.80; and n is 0 to 7.
[0121] The crystalline sorbent material is as described in relation to the first embodiment.
[0122] Suitably, in the use according to the fifth aspect, at least 10% by weight, suitably at least 15% by weight, such as at least 18% by weight, for example at least 20% by weight or at least 25% by weight of water is captured in 10 minutes, based on the weight of the crystalline sorbent material.
[0123] The inventors have discovered that the use of certain crystalline sorbent materials provides superior water delivery performance compared to known water sorbent materials, such as Syloid® Al-1. EXAMPLES
[0124] Materials and analytical methods The following materials were obtained from the stated sources: potassium hexacyanocobaltate(III) (K3[Co(CN)6]) - Alfa Aesar; zinc sulfate heptahydrate (Zn(SO4)2·7H2O) - Alfa Aesar; zinc nitrate hexahydrate (Zn(NO3)2·6H2O) - Sigma Aldrich; zinc chloride (ZnCl2) - Sigma Aldrich; and sulfuric acid (H2SO4, 95-97%) - Sigma-Aldrich. These materials were used directly without further purification. Millipore grade water was used in the synthesis of the materials in the examples described below. Zeolite 13X, Syloid® AL-1, and silica gel were obtained from commercial suppliers.
[0125] Powder X-ray Diffraction (PXRD) PXRD patterns were obtained using a PIXcel operated in scan line detector mode with an effective length of 4, using 255 channels. 3D The measurements were recorded at room temperature on a PANalytical Empyrean™ diffractometer equipped with a CuK detector. The diffractometer was equipped with an Empyrean Cu LFF (Long Fine Focus) HR (9430 033 7310x) tube operated at 40 kV and 40 mA. α Radiation (λ α =1.540598 Å) was used in the diffraction experiments. Data were collected using a continuous scan mode with a goniometer in the theta-theta direction. The incident beam optics was equipped with an anti-scatter slit PreFIX module, with a fixed divergence slit with 1 / 8° divergence slit and 1 / 4° anti-scatter slit, as well as a 10 mm fixed incident beam mask and Soller slit (0.04 rad). The divergent beam optics was equipped with a P7.5 anti-scatter slit, Soller slit (0.04 rad), and a Ni-β filter. In a typical experiment, approximately 20 mg of fine powder sample was loaded onto a zero background silicon disk. Data were collected from 5° to 45° (2θ) using a step size of 0.0131303° and a scan time of 30 s per step. Raw data was analyzed using X'Pert HighScore Plus™ software V4.1 (PANalytical, The Netherlands).
[0126] Figure 1 shows the structure of Zn[Co(CN)6] 0.667 4H2O (referred to herein as ZnCo) and a comparison with the experimentally obtained PXRD patterns described above for cubic and hexagonal phases of ZnCo.
[0127] In-situ variable temperature powder X-ray diffraction (VT-PXRD) The diffractograms at various temperatures were recorded using a PANalytical X'Pert Pro-MPD diffractometer equipped with a PIXcel3D detector operated in a scanning line detector mode with an effective length of 4, using 255 channels. Variable temperature diffractograms were recorded using an Anton Paar TTK450 stage coupled with an Anton Paar TCU110 temperature controller. The diffractometer was operated at 40 kV and 40 mA and CuKα radiation (λ α The instrument was equipped with a Cu LFF (Long Fine Focus) HR (9430 033 7300x) tube operated at θ = 1.54056 Å. Data were collected using a continuous scan mode with a goniometer in theta-theta direction. The incident beam optics was equipped with fixed divergence slits including a 1 / 4° divergence slit and a Soller slit (0.04 rad). The diverging beam optics was equipped with a P7.5 anti-scatter slit, Soller slit (0.04 rad), and a Ni-β filter. In a typical experiment, 50 mg of sample was dried, ground to a fine powder, and mounted on a sample holder fabricated in an Anton Paar TTK450 chamber. Data were collected from 5° to 40° (2θ) using a step size of 0.0167113° and a scan time of 50 s per step. Raw data were analyzed using X'Pert HighScore Plus™ software V4.1 (PANalytical, The Netherlands). Each sample was heated to 240° C. under a N2 atmosphere and then cooled to room temperature.
[0128] Thermogravimetric analysis (TGA) TGA thermograms were recorded under nitrogen using a TA Q50 V20.13 Build39 instrument. A platinum pan and a flow rate of 60 mL / min for nitrogen gas were used in the experiment. Data were collected in high-resolution dynamic mode with sensitivity of 1.0, resolution of 4.0, and a temperature gradient of 10°C / min up to 550°C. Data were evaluated using TA Universal Analysis for Windows XP / Vista 4.5A version.
[0129] ICP-OES analysis ICP-OES analysis was performed on an Agilent Technologies 5100 ICP-OES instrument. In a typical experiment, samples were prepared and analyzed as follows: 10 mg of each sample was dissolved in 4 mL of aqua regia. A 1 mL aliquot was removed from this solution and diluted with 34 mL of 1 M HNO. For each sample, three sets of aliquots were prepared and injected into the autosampler. Prior to analysis, the instrument was calibrated with standard solutions of all tested elements (Co, K, Zn, and S) in the appropriate concentration range (0-250 ppm). Individual elements were identified from peaks at characteristic positions (Co, 228 nm and 238 nm; K, 769 nm; Zn, 206 nm and 334 nm) with maximum intensity (to avoid interferences). The concentrations (ppm) of each element were calculated using the calibration curves and are summarized in Table 1 below.
[0130] Intrinsic Dynamic Vapor Sorption (DVS) measurements Water vapor sorption-desorption experiments at atmospheric pressure and 27°C were performed using a DVS Intrinsic analyzer (Surface Measurement Systems). Water vapor sorption isotherms were measured using approximately 5-30 mg of sample. HPLC-grade pure water was used as the sorbent in these measurements, and temperature was maintained by sealing the system in a temperature-controlled incubator. Prior to sorption analysis, each sample was pretreated at 40°C for 6 h, followed by cooling at 27°C for 60 min.
[0131] Vacuum DVS measurement Vacuum DVS measurements were performed using the Surface Measurement Systems DVS vacuum instrument. The DVS vacuum instrument used in these studies measures the absorption and loss of water vapor gravimetrically. Activated and degassed samples were placed under high vacuum (2·10 -6 Further in situ degassing at 37° C. (torr) to establish dry mass. Adsorption / desorption cycles were used to determine the recyclability and working capacity of ROS-038 and Syloid® AL-1, respectively.
[0132] The recycle tests were carried out in a temperature-controlled incubator at 27 °C. For each material, approximately 135 cycles of adsorption (0 → 60% P / P0, 5 min) followed by desorption (60 → 0% P / P0, 5 min) were performed at 27 °C. Approximately 5-10 mg of sample was used in each experiment. The mass of all samples was determined by comparison with an empty reference pan and recorded by a high-resolution microbalance with a mass resolution of ± 0.1 μg. The high mass resolution and its excellent baseline stability enable the device to measure the adsorption and desorption of extremely small amounts of water molecules. The vapor partial pressure around the sample is controlled by mixing saturated and dry carrier vapor flows using an electronic mass flow controller. The temperature was kept constant at 27 ± 0.1 °C by sealing the entire system in a temperature-controlled incubator. Pure water (HPLC gradient grade, Fisher Chemical) was used as the adsorbent in the recycle studies.
[0133] Intelligent Gravimetric Analyzer (IGA) Measurement Water vapor adsorption-desorption experiments at atmospheric pressure (1013 mbar, 760 Torr) were carried out using an IGAsorp Dynamic Vapor Sorption (DVS) analyzer from Hiden Isochema Ltd.UK. Prior to the experiments, the samples were allowed to reach temperature and humidity equilibrium in a chamber for a specific time. The samples (approximately 5-40 mg) were exposed to the desired %RH (30%RH, 60%RH, or 0%RH) and desired temperature in the adsorption (27°C) / desorption (49°C or 60°C) branches, respectively. Thus, the recyclability and regeneration profiles of water vapor adsorption and desorption were obtained.
[0134] Preparation of crystalline sorbent materials Example 1 K 0.10 Zn[Co(CN)6] 0.70 4H2O A solution of K3[Co(CN)6] (2 mmol, 664.6 mg) in 20 mL of H2O was added to a stirred solution of Zn(SO4)2·7H2O (2 mmol, 575.1 mg) in 20 mL of H2O. The resulting precipitate was stirred at room temperature for 30 min, filtered and washed with H2O. Yield: 530 mg, ca. 94%. The phase purity of the material was confirmed by identifying the respective PXRD peaks of PBA at 2θ(°) 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see FIG. 2). The composition of Example 1 was determined by ICP-OES analysis as described above and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0135] Example 2 K 0.009 Zn[Co(CN)6] 0.669 4.5H2O H3Co(CN)6 was synthesized from K3[Co(CN)6] by a previously reported procedure (US Pat. No. 7,022,641). H3Co(CN)6 produced by this method contained small amounts of potassium ion impurities (0.5-1%). A solution of H3[Co(CN)6] (containing 0.5-1% potassium relative to cobalt) (1 mmol, 218 mg) in 100 mL of H2O was added dropwise over 15 min to a stirred solution of Zn(SO4)2·7H2O (1 mmol, 287 mg) in 100 mL of H2O. The resulting precipitate was stirred at room temperature for 30 min, filtered, and washed with H2O. Yield: 250 mg, ca. 87%.
[0136] H3[Co(CN)6]K + As quantified by ICP-OES, it was found to be:
[0137] ICP-OES analysis of H3[Co(CN)6]: [Table 1]
[0138] Figure 2 shows a comparison of the calculated PXRD pattern for ZnCo (using data provided in Roque et al., 2007, cited above) with the PXRD patterns obtained by the above experiment for Example 1 (as-synthesized) and Example 9 (as-synthesized) measured at 25°C. The cubic phase purity of the material was confirmed by identifying the following characteristic PXRD peaks at the following 2θ (°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see Figure 2). The composition of Example 2 was determined by ICP-OES analysis as described above, and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0139] Example 3 K 0.02 Zn[Co(CN)6] 0.676 4.2H2O A solution of K3[Co(CN)6] (1 mmol, 332 mg) in 10 mL of H2O was added dropwise over 15 min to a stirred solution of Zn(NO3)2·6H2O (1.8 mmol, 535 mg) in 10 mL of H2O. The resulting precipitate was stirred at room temperature for 24 h, filtered, and washed with H2O. Yield: 400 mg, ca. 77%. The cubic phase purity of the material was confirmed by identifying the respective PXRD peaks of PBA at the following characteristic 2θ(°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see FIG. 2). The composition of Example 3 was determined by ICP-OES analysis as described above, and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0140] Example 4 K 0.03 Zn[Co(CN)6] 0.677 4H2O A solution of K3[Co(CN)6] (1 mmol, 332 mg) in 100 mL of H2O was added to a stirred solution of Zn(SO4)2·7H2O (1 mmol, 287 mg) in 100 mL of H2O. The resulting precipitate was stirred at room temperature for 30 min, allowed to stand for 24 h, then filtered and washed with H2O. Yield: 190 mg, ca. 66%. The cubic phase purity of the material was confirmed by identifying the respective PXRD peaks of PBA at the following characteristic 2θ(°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see FIG. 2). The composition of Example 4 was determined by ICP-OES analysis as described above, and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0141] Example 5 K 0.06 Zn[Co(CN)6] 0.688 3.5H2O 2.4 g of polyvinylpyrrolidone (PVP) was added to a solution of Zn(NO3)2·6H2O (0.71 mmol, 214 mg) in 80 mL of H2O and stirred until the solution was clear. To this, a solution of K3[Co(CN)6] (0.4 mmol, 132.9 mg) in 80 mL of H2O was added dropwise over 30 min. The resulting mixture was further stirred for 30 min, filtered, and washed with H2O. Yield: 150 mg, ca. 76%. The cubic phase purity of the material was confirmed by identifying the PXRD peaks of PBA at the following characteristic 2θ(°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, and 43.2 (see FIG. 2). The composition of Example 5 was determined by ICP-OES analysis as described above, and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0142] Example 6 K 0.11 Zn[Co(CN)6] 0.702 3.8H2O K3[Co(CN)6] (1.52 mmol, 521 mg) and ZnCl2 (2.28 mmol, 317 mg) were obtained as solids and 50 mL of H2O was added and stirred for 10 min. The resulting suspension was shaken on a benchtop shaker for 24 h (400 rpm). The slurry was centrifuged and the resulting solid was washed three times with distilled water and air-dried. Yield: 650 mg, approximately 98%. The cubic phase purity of the material was confirmed by identifying the PXRD peaks of PBA at the following characteristic 2θ (°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see FIG. 2). The composition of Example 6 was determined by ICP-OES analysis as described above and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0143] Example 7 K 0.12 Zn[Co(CN)6] 0.709 3.5H2O A solution of K3[Co(CN)6] (2 mmol, 664.6 mg) in 10 mL of H2O was added to a stirred solution of Zn(SO4)2·7H2O (2 mmol, 575.1 mg) in 10 mL of H2O. The resulting precipitate was stirred at room temperature for 30 min, filtered, and washed with H2O. Yield: 503 mg, ca. 89%. The cubic phase purity of the material was confirmed by identifying the PXRD peaks of PBA at the following characteristic 2θ(°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see FIG. 2). The composition of Example 7 was determined by ICP-OES analysis as described above, and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0144] Example 8 K 0.13 Zn[Co(CN)6] 0.711 4H2O A solution of K3[Co(CN)6] (2 mmol, 664.6 mg) in 5 mL of H2O was added to a stirred solution of Zn(SO4)2·7H2O (2 mmol, 575.1 mg) in 5 mL of H2O. The resulting precipitate was stirred at room temperature for 30 min, filtered, and washed with H2O. Yield: 540 mg, ca. 92%. The cubic phase purity of the material was confirmed by identifying the PXRD peaks of PBA at the following characteristic 2θ(°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see FIG. 2). The composition of Example 8 was determined by ICP-OES analysis as described above, and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0145] Example 9 K 0.25 Zn[Co(CN)6] 0.75 3.8H2O A solution of K3[Co(CN)6] (0.34 mol, 114.9 g) in 517 mL of H2O was added to a stirred solution of Zn(SO4)2·7H2O (0.34 mol, 99.42 g) in 517 mL of H2O. The resulting precipitate was stirred at room temperature for 4 h, filtered, and washed with H2O. Yield: about 100 g, about 98%. The cubic phase purity of the material was confirmed by identifying the PXRD peaks of PBA at the following characteristic 2θ(°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see FIG. 2). The composition of Example 9 was determined by ICP-OES analysis as described above, and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0146] Example 10 Scale-up synthesis of Example 1-K 0.10 Zn[Co(CN)6] 0.70 4H2O A solution of K3[Co(CN)6] (180 mmol, 59.81 g) in 1.8 L of H2O was added to a stirred solution of Zn(SO4)2·7H2O (180 mmol, 51.76 g) in 1.8 L of H2O. The resulting precipitate was stirred at room temperature for 30 min, filtered, and washed with H2O. Yield: 49.15 g, ca. 97%. The cubic phase purity of the material was confirmed by identifying the PXRD peaks of PBA at the following characteristic 2θ(°) positions: 14.9, 17.3, 24.5, 28.8, 35, 39.2, 43.2 (see FIG. 2). The composition of Example 10 was determined by ICP-OES analysis as described above, and the results are shown in Table 1. The number of water molecules was calculated from the TGA data.
[0147] Example 11 ROS038X paper composite was fabricated by using the materials prepared as described in Example 10.
[0148] A mixture of multiple cellulose and non-cellulosic fibers was combined with the sorbent material of Example 10, a proprietary binder (i.e., an acrylic-based binder system combined in whole or in part with a PVOH-based binder) and blended into a water slurry. The slurry was poured into a typical papermaking press with various stages of water removal by temperature and pressure applied to the slurry until a flat paper could be rolled for delivery to a rotor manufacturer. Figure 3 shows scanning electron microscope images (3 μm and 10 μm magnification) of this paper composite.
[0149] Comparative Example 1 ZnCo Aqueous Zn(SO4)2·7H2O (0.01M in 100mL H2O, 287mg) was mixed dropwise with H3[Co(CN)6] (0.01M in 100mL H2O, 218mg) and the resulting precipitate was stirred for 30min and left on the bench for 1week. The precipitate was separated from the mother liquor by centrifugation and the solids were washed with distilled water and then air dried. Yield, 230mg, ca. 81%. The phase purity of the material was confirmed by identifying the PBA peaks at 2θ(°) 14.9, 17.3, 24.5, 28.8, 35, 39.2 and 43.2 in the PXRD. X-ray dispersive energy spectroscopy (EDX) analysis showed that the atomic metal ratio (Zn:Co) was close to 3:2, which is in excellent agreement with the ZnCo reported in Roque et al. 2007 (cited above). The chemical composition was determined by ICP-OES analysis:
[0150] ICP-OES analysis of ZnCo: [Table 2]
[0151] EDX analysis of ZnCo: [Table 3]
[0152] Comparative Example 2 Zinc 3-a Fe a [Co(CN)6]2·nH2O-FeZnCo A solution of K3[Co(CN)6] (1 mmol, 332.33 mg) in 100 mL of H2O was added to a mixed solution of FeSO4·7H2O (1.8 mmol, 501 mg in 100 mL of H2O) and Zn(SO4)2·7H2O (3.6 mmol, 1.036 g in 100 mL of H2O). The resulting precipitate was filtered by using a membrane filter paper and washed with distilled H2O. Yield, 310 mg, ca. 77%. The phase purity of the material was confirmed by identifying the PBA peaks at 2θ(°) 14.9, 17.3, 24.5, 28.8, 35, 39.2, and 43.2 in the PXRD. The chemical composition was determined by ICP-OES analysis:
[0153] ICP-OES analysis of ZnFeCo: [Table 4]
[0154] [Table 5]
[0155] Performance Testing Thermal Stability Test The thermal stability of the cubic phase of the material of Example 1 (designated ROS-038X) was confirmed by variable temperature powder X-ray diffraction (VT-PXRD) in the range of 25°C to 240°C. Figure 4 shows the VT-PXRD patterns (measured under N2 flow) of Example 1 from 25°C to 240°C, obtained as described above. The results confirm that the cubic phase of Example 1 is stable even at 240°C in air and under vacuum. The unit cell was observed to shrink slightly after losing water molecules at approximately 80°C.
[0156] Water Vapor Sorption Studies – Water Absorption Water sorption isotherms were collected at 27° C. and humidity range of 0-90% RH using an SMS Intrinsic DVS instrument as described above. FIG. 5 shows water sorption isotherms of Example 1 (ROS-038X), Example 9 (ROS-038Y), Syloid® AL-1, and Zeolite 13X measured at 27° C. Colored and uncolored symbols represent the adsorption and desorption branches, respectively. Instrument: Intrinsic-DVS.dm / dt(% / min)<0.05. FIG. 6 shows the K of the exemplary materials of Examples 1-9. + The water absorption (at 60% RH and 27° C.) in weight percent versus content is shown. Examples 1-6 (referred to as ROS-038X materials) were found to exhibit higher water absorption than Examples 7-9 (referred to as ROS-038Y materials) (see FIG. 5). + A correlation between the content and water absorption was evident (FIG. 6). In particular, the K range of 0.009 to 0.12 in Examples 1 to 6 was + In terms of content, the water absorption was about 30% by mass. + A decrease in water absorption was observed above =0.12, indicating that the ROS-038X and ROS-038Y materials have different structures (or phases).
[0157] As revealed by the results of FIG. 5, ROS-038X material Example 1 adsorbs about 30% by weight at 60% RH and about 27% by weight at 30% RH. To evaluate the performance of ROS-038X as a desiccant relative to commercially used materials, zeolite 13X and Syloid® AL-1 were tested under the same conditions. Syloid® AL-1 showed a water absorption of about 30% by weight at 60% RH and about 14% by weight at 30% RH, as well as an isotherm profile that is less suitable for its intended purpose, which is effective water vapor sorption. Notably, the water absorption of Example 1 (ROS-038X) is twice that of Syloid® AL-1 at 30% RH. Another commercially available desiccant, zeolite 13X, showed a water absorption of about 5% by weight at 30% RH and about 7% by weight at 60% RH, which is significantly lower than the values measured in Example 1 (ROS-038X).
[0158] For comparison, the ZnCo and FeZnCo materials were similarly tested for their water sorption performance. The results are shown in Figures 7 and 8. The ZnCo material performed similarly to ROS-038X, but is, of course, thermally unstable and therefore less effective in most practical applications. The FeZnCo material exhibited significantly lower water sorption than ROS-038X.
[0159] Water Vapor Sorption Study - Recyclability Sorbent recyclability tests simulating the vacuum swing method (test conditions: adsorption 0→60%P / P0, 5 min; desorption 60→0%P / P0, 5 min) were performed at 27° C. using the SMS vacuum-DVS on the material of Example 1 using the procedure described above. FIG. 9 shows the results of these water cycling tests of Example 1 (ROS-038X) for 135 cycles. Adsorption conditions were 0%P / P0 to 60%P / P0 at 27° C. over 5 min. Desorption conditions were 60%P / P0 to 0%P / P0 at 27° C. over 5 min. Prior to starting the cycling tests, the samples were pre-activated in-situ in the vacuum-DVS instrument at 0%P / P0 and 50° C. for 3 h and at 27° C. for 1 h. Mass at the end of the first 0%P / P0 step: 5.3 mg. In a 10 minute cycle of adsorption / desorption, Example 1 (ROS-038X) exhibited a working capacity of 30 wt. % while maintaining performance for >135 cycles (see FIG. 9). Under the same conditions, Syloid® AL-1 exhibited a working capacity of 23 wt. %. Example 1 (ROS-038X) therefore has a higher working capacity than Syloid® AL-1. The comparative FeZnCo sorbent material was similarly tested and the results are shown in FIG. 10.
[0160] Paper composite Example 11 was made as above using the material of Example 10 (ROS-038X) and tested using the SMS vacuum-DVS under the same conditions used for the Example 1 (ROS-038X) powder above. Figure 11 shows these water cycling experiments of Example 11 (ROS-038X) paper composite for 135 cycles. Adsorption conditions were 0% P / P0 to 60% P / P0 at 27°C over 5 minutes. Desorption conditions were 60% P / P0 to 0% P / P0 at 27°C over 5 minutes. Prior to starting the cycling test, the paper was pre-treated in-situ in the vacuum-DVS instrument at 0% P / P0 and 50°C for 3 hours and at 27°C for 1 hour. Mass at the end of the first 0% P / P0 step: 6.6 mg. As shown in FIG. 11, the working capacity of ROS-038X Paper Example 11 is approximately 21% by weight, and that performance is maintained for >135 cycles.
[0161] Sorbent recyclability tests simulating temperature and humidity swings mimicking an actual recycling process were performed on the material of Example 1 (ROS-038X) and Syloid® AL-1 using an IGA vapor sorption analyzer using the procedure described above. Figure 12 shows the comparative results of these water cycling experiments for Example 1 (ROS-038X) versus Syloid® AL-1 for 17 cycles. The adsorption conditions were 0% RH to 60% RH at 27°C over 14 minutes. The desorption conditions were 60% RH to 0% RH at 49°C over 20 minutes (Figure 12). Before starting the cycling test, the samples were pre-activated in-situ in the IGA instrument at 0% RH and 50°C for 1 hour under dry air and at 27°C for 1 hour. End mass of the first 0% RH step: 6.5 mg. In a 34 minute cycle of adsorption / desorption, Example 1 (ROS-038X) exhibits a working capacity of 30.2 wt % (at 49° C.) but maintains performance for >17 cycles (see FIG. 12, Table 2). Under the same conditions, Syloid® AL-1 exhibited a working capacity of 14.6 wt % (see FIG. 12, Table 2). The water deliverability over time (L / (kg·day)) for each of these materials is shown in Table 2. Thus, Example 1 (ROS-038X) has superior working capacity and water deliverability (12.79 L / (kg·day)) compared to Syloid® AL-1 (6.17 L / (kg·day)).
[0162] [Table 6]
[0163] Temperature and humidity swing recycling tests were performed on paper composite Example 11 (made using the material of Example 10 (ROS-038X)) using an IGA vapor sorption analyzer under the same conditions as those used for the Example 1 (ROS-038X) powder above. Figure 13 shows these water cycling experiments of the Example 11 (ROS-038X) paper composite for 17 cycles. The adsorption conditions were 0% RH to 60% RH at 27°C over 14 minutes. The desorption conditions were 60% RH to 0% RH at 49°C over 20 minutes. Before starting the cycling test, the paper composite was pre-treated in-situ in the IGA apparatus at 0% RH and 50°C under dry air for 3 hours and at 27°C for 1 hour. End mass of the first 0% RH step: 7.8 mg. As shown in Figure 13 and Table 2, the working capacity (wt%) of ROS-038X-paper composite Example 11 is about 21.3 wt%, and its performance is maintained for >17 cycles. The water deliverability is 9.04 L / (kg day).
[0164] Therefore, ROS-038X material exhibits superior water harvesting and dehumidification performance compared to leading commercial desiccants. Furthermore, these results demonstrate that ROS-038X material can be prepared at scale by a green synthesis method (slurrying in water), a key requirement for large-scale manufacturing and end-use applications of desiccants.
[0165] In summary, the present invention provides crystalline sorbent materials for use as water capture materials that have favorable water absorption capacity and sorption / desorption kinetics, while at the same time having structural stability and recyclability of water capture over many cycles. Furthermore, the crystalline sorbent materials described herein can be obtained on a large scale from processes that have low environmental impact. Thus, the crystalline sorbent materials of the present invention can provide sorbent materials for water capture processes that are more advantageous than known sorbent materials.
[0166] While several preferred embodiments have been shown and described, it will be understood by those skilled in the art that various changes and modifications can be made without departing from the scope of the invention, as defined in the appended claims.
[0167] Throughout this specification, the terms "comprising" or "comprise" mean the inclusion of the specified component, but do not exclude the presence of other components. The terms "consisting essentially of" or "consist essentially of" mean the inclusion of the specified component, but excluding other components, except for materials present as impurities, unavoidable materials present as a result of the process used to produce the component, and components added for purposes other than achieving the technical effect of the invention. Typically, when referred to as a composition, a composition consisting essentially of a set of components will contain less than 5% by weight, typically less than 3% by weight, and more typically less than 1% by weight of the unspecified component.
[0168] The terms "consisting of" or "consist of" mean the inclusion of certain components but to the exclusion of the addition of other components.
[0169] Where appropriate, depending on the context, use of the terms "comprise" or "comprising" can also be considered to encompass or include the meaning of "consist essentially of" or "consisting essentially of" and to include the meaning of "consist of" or "consisting of."
[0170] For the avoidance of doubt, amounts of components in a composition are listed in weight percent, which means the weight percent of the particular component relative to the total composition being referred to. For example, "a sorbent composition comprising 10-90 weight percent of a crystalline sorbent material" means that 10-90 weight percent of the sorbent composition is provided by the crystalline sorbent material.
[0171] Any features described herein may be used individually or, where appropriate, in combination with one another, particularly in the combinations described in the appended claims. Any feature of each aspect or exemplary embodiment of the present invention described herein should also be read as applicable to any other aspect or exemplary embodiment of the present invention, where appropriate. In other words, a person skilled in the art reading this specification should consider any feature of each exemplary embodiment of the present invention as interchangeable and combinable between various exemplary embodiments.
[0172] All articles and documents related to this application that are filed contemporaneously with and prior to this application and that are open to public inspection herewith are noted, and the contents of all such articles and documents are incorporated herein by reference.
[0173] All of the features disclosed in this specification (including the accompanying claims and drawings), and / or all of the steps of any method or process similarly disclosed, may be combined in any combination, except combinations in which at least some of such features and / or steps are mutually exclusive.
[0174] Each feature disclosed in this specification (including any accompanying claims and drawings), unless expressly stated otherwise, may be replaced by alternative features serving the same, equivalent or similar purpose. Thus, unless expressly stated otherwise, each feature disclosed is merely an example of a generic series of equivalent or similar features.
[0175] The invention is not limited to the details of the foregoing embodiments. The invention extends to any novel, or any novel combination of, features disclosed in this specification (including any accompanying claims and drawings), or to any novel, or any novel combination of steps of any method or process similarly disclosed.
Claims
1. formula: A b M’[M(CN) 6 ] y ・nH 2 O where A is a Group 1 metal; b is 0.001 to 0.3; M' is zinc; M is iron or cobalt; y is 0.65 to 0.80; and n is 0 to 7. Crystalline sorbent material.
2. 2. The crystalline sorbent material of claim 1, wherein A is potassium.
3. 2. The crystalline sorbent material of claim 1, wherein M is cobalt.
4. Formula (K b Zn[Co(CN) 6 ] y ・nH 2 2. The crystalline sorbent material of claim 1 having the formula: O) where b is 0.001 to 0.3, y is 0.65 to 0.80, and n is 0 to 7.
5. The crystalline sorbent material of claim 4, wherein b is from 0.005 to 0.
12.
6. The crystalline sorbent material of claim 4, wherein b is from 0.12 to 0.
3.
7. 10. The crystalline sorbent material of claim 1 having a cubic unit cell.
8. 2. The crystalline sorbent material of claim 1 which is thermally and / or hydrolytically stable, preferably the crystalline sorbent material does not undergo a phase transition to a hexagonal phase when heated to at least 80°C.
9. 13. A method for preparing the crystalline sorbent material of claim 1, comprising the steps of: (a) B c [M (CN) 6 ]Source M'X x reacting with a source; and (b) obtaining said crystalline sorbent material; Including, wherein B is H or a Group 1 metal; c is 2-4; M' is zinc; M is iron or cobalt; X is an anion; and x is 1-4.
10. Step (a) is a step of mixing the B c [M (CN) 6 ] source and M'X x 10. The method of claim 9, wherein: step (b) comprises precipitating said crystalline sorbent material from water.
11. 1. A method for capturing water from a composition containing water and / or water vapor, the method comprising: (i) Formula A b M' [M (CN) 6 ] y ・nH 2 providing a crystalline sorbent material of O; and (ii) contacting the crystalline sorbent material with the composition comprising water; Including, wherein upon contact with said composition comprising water and / or water vapor, said crystalline sorbent material sorbs water; wherein A is a Group 1 metal; b is 0.001 to 0.3, M' is zinc, and M is iron or cobalt; y is 0.65 to 0.80; and n is 0 to 7.
12. 12. The method of claim 11, wherein the composition is a gas composition comprising water, preferably the gas composition is air.
13. 13. A method according to claim 11 or 12, comprising the further step (iii) of releasing the trapped water from the crystalline sorbent material using a suitable method such as a temperature swing, a humidity swing, or a vacuum swing.
14. The method of claim 11 , wherein the crystalline sorbent material is provided on a support.
15. 1. A method for delivering water to a location from a composition comprising water or water vapor, the method comprising: (1) Formula A b M' [M (CN) 6 ] y ・nH 2 providing a crystalline sorbent material of O; (2) contacting the crystalline sorbent material with water or water vapor to entrap water in the crystalline sorbent material; (3) optionally transporting and / or storing the crystalline sorbent material; (4) applying a stimulus to the crystalline sorbent material to effect desorption of water retained in the crystalline sorbent material; and (5) recovering the desorbed water at the predetermined location; Including, A method according to the invention, wherein A is a Group 1 metal; b is 0.001 to 0.3; M' is zinc; M is iron or cobalt; y is 0.65 to 0.80; and n is 0 to 7.
16. For capturing water or water vapor from a composition containing water, a compound of formula A b M' [M (CN) 6 ] y ・nH 2 The present invention relates to the use of a crystalline sorbent material of the formula: O (wherein A is a Group 1 metal; b is 0.001-0.3; M' is zinc; M is iron or cobalt; y is 0.65-0.80; and n is 0-7).
Citation Information
Patent Citations
Solvation methods, apparatus, and systems
JP2007526110A
Lithium ion secondary battery electrode material using prussian blue analog
JP2011246303A
Mixed valence metal sulfide sorbent for heavy metals
JP2012515645A
Ammonia adsorbent
WO2015186819A1